Better regulation in Europe : Italy 2012 - Organisation for Economic Co-operation and Development (OECD, 2013)
Summary.
Keywords: sääntely : Italia; hallinnon uudistaminen : Italia; säädösvalmistelu : Italia; oikeuspolitiikka : Italia; EU-oikeus : valtionsisäinen oikeus : Italia; avoimuus : Italia